Changes in total factor productivity and its causative factors in Japanese agriculture - Yoji Kunimitsu (European Regional Science Association (ERSA), 2011)
Agricultural public facilities for irrigation and drainage play an important role in Japanese agriculture, especially in paddy production. However, the budget for renovation of old facilities was drastically cut in 2010. For prolonging life time and decreasing lifecycle costs of public facilities, the asset-management measures (AMMs), which reinforce old facilities in stead of reconstruction, have started. This study analyzes effects of the AMMs by the recursive dynamic computable general equilibrium (CGE) model. Simulation results demonstrated that, firstly, the AMMs increased not only agricultural production but also food production via reallocation of production factors and prices. Second, the increase in GDP improved consumption and private investment via an increase in labor income, and decreased the general price of goods and service. Third, consumer price went down and consequently Hicksian Equivalent Variation value, which shows social and economic effects, increased. In this sense, the AMMs bring about positive ripple effects to economies. The dynamic CGE model can also measure such long-term comprehensive effects and is useful for policy analysis.
Keywords: 330